The Filipino Contemporary Arts Centrum - Batac, Lea Francesca F.; Bulaong, Carmen Bettina (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The Philippine contemporary arts lacks support from the local community and is often overlooked by the government and the society. This lack of support results to the underutilized potentials of the contemporary arts to the socio-economic development of the country. Because of the limited and inefficient infrastractures to facilitate and showcase the Philippine contemporary arts, the impact is mostly on two entities : (1) the Filipino creative clusters, whose artworks are either exhibited, or displayed improperly and ineffectively resulting to the depreciation of their value; (2) the general public, as they continue to underappreciate and remain to neglect the potentials of the country's contemporary culture. This study aims to formulate an innovative design approach for an architecture that shall give solutions to the said issues and change the perspective of the Filipinos and the world at large regarding the Filipino contemporary arts and culture. This is a proposal for the Filipino Contemporary Arts Centrum. A "centrum" is anatomically defined as the solid central part of a vertebra to which the arches and processes are attached. When applied to the title Filipino Contemporary Arts Centrum, it implies a characteristic of being a core, home, or center for both the artists and their artworks, wherein various genres, concepts, and media of expression of the contemporary arts branch out. The proposed Filipino Contemporary Arts Centrum serves as a monument of Filipino pride and a medium to regenerate the Philippines' cultural growth.
Includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman